The Snow-Capped Mountain and the Uranium Mine: Zuni Heritage and the Landscape Scale in Cultural Resource Management. Issue 4 (August 2014) - Colwell, Chip; Ferguson, T. J.
Abstract: Known in English as Mount Taylor, Dewankwin Kyaba:chu Yalanne ("in the east snow-capped mountain") in northwestern New Mexico is a sacred landscape to the Zuni people. From an archaeological perspective, the mountain is dotted with hundreds of discrete archaeological sites that record 12, 000 years of history. From a Zuni perspective, Mount Taylor is a rich cultural landscape—a tangible record of ancestral migrations, a living being, a pilgrimage site, a referent in religious prayers, a spiritual source of rain, and a collecting place for spring water, animals, minerals, and plants. For Zunis, all of these facets of the mountain combine to create a "total landscape" that is both a source and an instrument of Zuni culture. This article presents a case study of a compliance project to document the potential impacts of a proposed uranium mine at the base of Mount Taylor on Zuni traditional cultural properties. The project demonstrates how archaeologists can benefit from a landscape perspective that builds from the traditional knowledge of descendant communities. The Zuni standpoint further helps shape a CRM practice that is anthropologically informed and consistent with a developing federal mandate to use landscape-scale analysis in heritage management and mitigation practices.